ANALISIS PERTUMBUHAN KONSUMSI PRODUK HALAL DI BERBAGAI SEKTOR EKONOMI INDONESIA HINGGA TAHUN 2025 - Maya Utami; Cahaya Aqila; Putri Andini; Yenni Samri Julianti Nasution (J-EBI Jurnal Ekonomi dan Bisnis Islam, 2024)
The increasing demand for halal products is in line with the growth of the Muslim population and public awareness of the importance of halal products, as well as policy support from the government. Halal products now cover a wider range of sectors, such as food, cosmetics, pharmaceuticals, tourism and finance. This literature research was carried out using secondary data analysis methods obtained from various literature sources, industry reports, and previous academic research discussing the development of halal products globally and in Indonesia. The literature analyzed includes the halal concept, global halal economic growth, related government policies, and the role of regulations in encouraging the consumption of halal products. The research results show that consumption of halal products is expected to increase significantly, reaching a total of US$282 billion, which marks a 53% increase in consumption value in 2020. The food and beverage sector is the largest contributor to this growth, with a projected increase of US$135 billion in 2020 to US$204 billion in 2025. Apart from that, the media and recreation sector also shows significant growth. Even though the tourism sector has experienced negative impacts due to the pandemic, it is hoped that this sector will recover along with the recovery of the post-pandemic tourism industry.